2012
DOI: 10.1001/archneurol.2012.70
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Ocular Tremor in Patients With Parkinson Disease

Abstract: Patients: One hundred twelve patients with PD, including 18 de novo untreated patients, and 60 age-matched controls. Intervention: Modern, precise eye tracking technology was used to assess oculomotor parameters. Oculomotor function was compared between groups during fixation and while tracking a randomly displaced target on a PC monitor. Main Outcome Measures: Fixation stability and saccadic parameters. Results: All patients with PD and 2 of 60 control subjects showed oscillatory fixation instability (ocular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 23 publications
3
65
2
Order By: Relevance
“…Recent controversy has arisen over the report of ocular tremor in Parkinson’s disease (PD) patients by Gitchel et al[69] They report a pervasive ocular tremor with an average fundamental frequency of 5–6 Hz and mean horizontal amplitude of 0.27 degrees. This tremor was reported in all 112 patients in the study, hence it was deemed pervasive, and it was suggested that further investigations could lead to use of this ocular tremor as an early diagnostic marker for PD.…”
Section: Ocular Tremor In Parkinson’s Diseasementioning
confidence: 99%
“…Recent controversy has arisen over the report of ocular tremor in Parkinson’s disease (PD) patients by Gitchel et al[69] They report a pervasive ocular tremor with an average fundamental frequency of 5–6 Hz and mean horizontal amplitude of 0.27 degrees. This tremor was reported in all 112 patients in the study, hence it was deemed pervasive, and it was suggested that further investigations could lead to use of this ocular tremor as an early diagnostic marker for PD.…”
Section: Ocular Tremor In Parkinson’s Diseasementioning
confidence: 99%
“…Gitchel and colleagues studied the eye movements of 112 patients with idiopathic PD during steady fixation (15). They identified a continuous oscillatory fixation instability that they termed “pervasive ocular tremor” in every PD patient.…”
Section: “Pervasive Ocular Tremor” In Pdmentioning
confidence: 99%
“…The oscillations had an average fundamental frequency of 5.7 Hz (i.e., within the range of the limb tremor in PD; 4–7 Hz), a mean horizontal amplitude of 0.27°, and mean vertical amplitude of 0.33°. The tremor persisted for the duration of the recording, although the waveform characteristics were variable (15). Figure 1 taken from the original manuscript shows a typical 1.2 s recording of the ocular tremor.…”
Section: “Pervasive Ocular Tremor” In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Fixational eye movements are characteristically unstable in PD, with more frequent small saccadic intrusions and tremor than in healthy controls. 24,25 Larger-amplitude square-wave jerks-saccades of similar magnitude, going into opposite directions, separated by a brief time interval-have particularly been found in patients with progressive supranuclear palsy (PSP) and other Parkinsonian movement disorders, 24,26,27 but also in PD patients.…”
mentioning
confidence: 99%